Evaluasi Perawatan Fasilitas Sisi Udara (Air Side) Di Bandara Juanda Surabaya - Yati Nurhayati (WARTA ARDHIA, 2011)
Evaluation of air side facility (runway sweeper) maintenance at Juanda airport in Surabaya is to know whether the air side facility (runway sweeper) maintenance system at Juanda airport in Surabaya meets the maintenance standard which is set by the Directorate General of Civil Aviation and still qualify to be operated. Assessment method used is descriptive qualitative method; detailed explanation based on the compilation of primary data and secondary data which have been processed. The results show that runway sweeper equipment maintenance done by technician at Juanda airport in Surabaya is still less than the maximum level according to the procedures established by the Directorate General of Civil Aviation about equipment maintenance.